PENGARUH KUALITAS LAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN (Studi pada Bengkel Mobil Astra Bayerische Motoren Werke Semarang) (Students' Journal of Economic and Management, 2015)
This study aimed to analyze the influence of service quality and corporate image on customer satisfaction Astra car workshop Bayerische Motoren Werke Semarang. The data used is primary data obtained directly from the customer in the form of a questionnaire. The sampling technique is purposive sampling. Based on purposive sampling, then obtained a sample of 100 people. Test equipment used in this study testing the validity of using the Pearson correlation, using Cronbach Alpha reliability testing and hypothesis testing using multiple linear regression. The results of the analysis can be concluded that: (1) The quality of service has positive influence on customer satisfaction. The higher the quality of service received, the customer satisfaction will increase. (2) The image of the company positive effect on customer satisfaction. The better the image of the company, the customer satisfaction will increase. Keywords: Quality of Service, Corporate Image and Customer Satisfaction